2008
DOI: 10.1016/j.diagmicrobio.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A line immunoassay utilizing recombinant nucleocapsid proteins for detection of antibodies to human coronaviruses

Abstract: Most coronaviruses infecting humans cause mild diseases, whereas severe acute respiratory syndrome (SARS)-associated coronavirus is an extremely dangerous pathogen. Here, we report the development of a serologic assay for detection of antibodies to human coronaviruses (HCoVs) based on recombinant nucleocapsid (N) proteins of all known pathogenic strains (229E, NL63, OC43, HKU1, SARS). The novel immunoassay is highly useful for epidemiologic surveys, where use of nucleic acid diagnostics often is limited. Purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 42 publications
5
32
0
Order By: Relevance
“…Indeed, the results presented in this study showed that approximately 90% of serum samples from young adults and middle-aged and elderly patients with respiratory infections reacted strongly to the HCoV-OC43 NPs, indicating prior exposure to this disease. This finding is consistent with previous epidemiological surveys that concluded that seroprevalence increases rapidly during childhood, attaining a seroprevalence rate of up to 90% in adults (Lehmann et al, 2008;Mourez et al, 2007). Additionally, antibodies against HCoV-OC43 NP were detected in over 90% of cord blood samples tested.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the results presented in this study showed that approximately 90% of serum samples from young adults and middle-aged and elderly patients with respiratory infections reacted strongly to the HCoV-OC43 NPs, indicating prior exposure to this disease. This finding is consistent with previous epidemiological surveys that concluded that seroprevalence increases rapidly during childhood, attaining a seroprevalence rate of up to 90% in adults (Lehmann et al, 2008;Mourez et al, 2007). Additionally, antibodies against HCoV-OC43 NP were detected in over 90% of cord blood samples tested.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas cross-reactivity between the SARS-CoV NP and the anti-HCoV-229E antibody or the anti-HCoV-OC43 antibody has been reported , high-titre anti-HCoV-OC43 NP polyclonal antibody did not cross-react with other human CoV NPs, including those of SARS-CoV and HCoV-229E, despite the presence of highly conserved motifs in these coronavirus NPs. Previous studies also showed that the anti-SARS CoV NP and anti-HCoV-229E NP polyclonal antibodies did not cross-react with other human CoV NPs Lee et al, 2010;Lehmann et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…16 Given the shared structural and functional domain features among coronavirus N proteins we applied the same approach for HCoV-OC43 and HCoV-HKU1, since crossreactivity by the antibodies directed to the full-N of HCoV-OC43 and HCoV-HKU1 has been reported in human sera. [16][17][18] The HCoV-NL63 and HCoV-229E recombinant NCt proteins were produced as previously described. 12 The generation of the plasmid for NCt-OC43 and NCt-HKU1 was performed using the same method.…”
Section: Generation and Expression Of Recombinant Hcov Carboxyl-termimentioning
confidence: 99%
“…Early methods for the detection of the four HCoVs included serologic analysis, virus culture, and/or antigen detection [18,19,20]. However, these methods were often time-consumingand low sensitive, and easily caused cross-reaction with other HCoVs [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%